أثر الاندماج والاستحواذ على الأداء المالي للمصرف دراسة حالة: مجموعة عوده سرادار المصرفية للخدمات الخاصة - ضاهر حنان (Latakia University Journal - Economic and Legal Sciences Series, 2016)
تعد عمليتا الاندماج والاستحواذ خياراً له الأولوية بالنسبة للبنوك حتى تنمو وتزداد حجماً. حصلت على أهميتها في عالم الشراكة اليوم نظراً للمنافسة الشديدة في بيئة الأعمال. في هذه الورقة محاولة لتقييم أثر الاندماج على الأداء المالي لبنك سرادر الذي اندمج مع بنك عوده في العام 2004 لتشكيل مجموعة عوده سرادار المصرفية للخدمات الخاصة. وسيتم التقييم باستخدام أحدث نموذج للتحليل المالي – نموذج CAMEL والذي يقيس أداء البنوك بالاعتماد على معايير مثل ملاءة رأس المال، جودة الأصول، كفاءة الإدارة، جودة الأرباح والسيولة. امتدت فترة الدراسة من العام 2000 وحتى نهاية العام 2008. تم تقسيم فترة الدراسة إلى فترة قبل الدمج وفترة بعد الدمج. جمعت بيانات الدراسة بشكل أساسي من التقارير السنوية. أظهرت نتائج الدراسة تحسن الأداء المالي لبنك سرادار في مرحلة بعد الدمج وذلك بالنسبة لمعظم مؤشرات نموذج CAMEL. The merger and acquisition operations has been preferred choice for banks to grow and becoming big .It got its importance in the world of partnership today due to the sever competition in the business environment. This paper is an attempt to evaluate the impact of merger on the financial performance of bank Sradar that merged with bank Audi in 2004 to formulate the Audi-Sradar banking group for private services. The evaluation is conducted by applying the most recent model for financial analysis-the CAMEL model- that measures the bank performance based on indicators such as the adequacy of capital, the quality of assets, the efficiency of management, the quality of earnings and liquidity. The study spans the period from 2000 to 2008. The study period is divided into the pre and post merger periods. The data is primarily collected from the annual reports. The results reveal that there is an improvement in the financial performance of Sradar bank in the post merger period for most of the indicators in the CAMEL model.